NAVIGATING THE MODERN BANKING LANDSCAPE IN INDIA: TECHNOLOGICAL ADVANCEMENTS AND LEGAL CHALLENGES - Tomer, Abhinav; Gautam, Jitendra Kr (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The banking system in India is transforming day by day and it is ultimately growing day by day. The banking sector has changed completely from the traditional banking system to modern banking system, and now things have also changed by the intrusion or infiltration of the mainstream i.e with the traditional banking banking process. It is where the bankers provide the services using modern technology or digitization.